Whistleblowing System in Forensic Audit for Fraud Disclosure - Suryani, Irma; Setiawan, Amelia; Djajadikerta, Hamfri (Fakultas Ekonomi Universitas Garut, 2024)
Business competition makes companies must be able to maintain their survival, but fraud that occurs can result in high risks for the company so that it needs to be anticipated and managed properly. This study intends to examine the role of the whistleblower system in the implementation of forensic audits, particularly in effort to reveal fraud. The approach employed in this research is a Literatire Review (SLR) study employing data sources from various national and international research.The results showed that the whistleblowing system has an important role as a provider of initial information about fraud that occurs in an organisation in both the government and private sectors. Information obtained from whistleblowers can then be used as preliminary evidence for auditors to conduct investigative audits and forensic audits that pay attention to the interests of evidence based on the law.This study also found that whistleblowers are more comfortable disclosing fraud to external parties than to internal organizations and are more willing to disclose fraud information if the fraud is committed by peers and equals than if it is committed by leaders or top management.